A comparative study of the seedling production technology of Picea obovata L. in the forest-steppe ecotone of northern Mongolia - Damdinjamts, Jagdag; Ganbaatar, Batsaikhan; Nachin, Baatarbileg; Erdenechuluun, Naranbayar; Dashzeveg, Ganbat; Altanhuyag, Bayartulga; Sukhbaatar, Gerelbaatar (Proceedings of the Mongolian Academy of Sciences, 2021)
The success of reforestation largely depends on the quality of the seedling. This study focuses on comparative assessments of the experimental planting of Picea obovata seedlings under various growing conditions, including in a greenhouse and open field. The objectives were to carry out a comparative study of the effect of different care regimes on the growth of seedling, and to choose the most optimal treatment that accelerates the growth of seedlings on the basis of the results taken from the comparative analysis. The study was carried out in the Experimental Forest Nursery of the Institute of Geography and Geoecology, MAS in the period between 2018 and 2020. The experimental planting design included four treatments with varying irrigation norms, air temperatures, air relative humidity, shading rates. Two of these experiments were put in greenhouses, and the remaining two treatments were in the open field. Repeated measurements and sampling were performed at the end of each growing season. The results showed high variation in seedling height (p < 0.0001; F = 38.6) and diameter (p < 0.0001; F = 43.2) growth and biomass accumulation (p < 0.0001). These variables therefore, positively corresponded to the air temperature, air relative humidity and moisture sufficiency in the soils. We found that the seedlings had faster growth in height (52.4%) and diameter (62.3%), and there was more biomass accumulation (128.1%) under greenhouse conditions than outdoors. With regard to the biomass allocation, a three-year observation showed a greater proportion of stem biomass in the total biomass, and, conversely, the predominant proportion of needle biomass accounted for open field treatments. However, the creation of stable condition in the greenhouse with a high relative humidity (more than 75%; daily watering norm of 20 liters per day) and an internal temperature of 25°C (40% shading) had the most positive effect on the growth and accumulation of biomass of seedlings. Consequently, we conclude that to meet the existing needs for seedlings for the restoration of natural Picea obovata forests, seedling production in greenhouses should be recommended.